Creating Sign and reading strategy in the deconstructing critism of Derrid - Shbani , Monzer (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research attempts at focusing on the sing concept by the French philosopher Jacques Derrida and how he tried to present a different critical reading of this concept, busy answering the question and looking for new horizons of this critical reading that gose beyond the structural closure. this will be through a reading strategy that enables us to open up to the text and its multiplicities. So this research firstly introduces the concept as done by Derrida then proceeds to discuss the role of reader being one deadly strategy in creating or producing the sing, being one product of the text, and his ability to recall the memory. All of this is to clarify the distance among texts which the textual horizon creates, since its role dose not have to do only with the strength of sing as in difference but also it contains a structural motive.The sign is created once the effect and the one who is put away are traced down and thus creates enterainment among texts. Consequently, reading becomes an aesthetic experience that reconstructs the text anew till we get in this research to accumulative results in a conclusion that presents some of the ideas we ended up with when tacking this issue. .